Chapter Appendice. Per una nuova filosofia della cittadinanza - Caruso, Sergio (Studi e saggi, 2023)
Sergio Caruso conceives citizenship not only as a set of rights and duties related to belonging to a political community but also as a bundle of social functions, in which next to the citizen-voter there is the citizen producer, consumer, taxpayer, user, and so on. And it proposes new forms of political participation linked to this plurality of citizenship declinations to complement political democracy.